Teologi Hari: Analisis Teologi Kritis Terhadap Waktu Dalam Lontar Aji Swamaṇḍala - Wasudewa Bhattacarya; I Ketut Donder; I Wayan Redi (Jayapangus Press, 2019)
This research was conducted on the interest of the writer of Wariga in Bali. Wariga is when adjusted to the Hindu Theological derivation is very compatible with Theology Day, because in it contains about God's involvement in any time or day that can affect human life. Nowadays, the understanding of Wariga and Hindu theology is still low, therefore it is important to describe and analyze critically the Theology Day that exist in manuscript, especially Lontar Aji Swamaṇḍala. The results of this research are the teachings contained in Lontar Aji Swamaṇḍala includes (1) Widhi, (2) Manusya, (3) Mukti, and (4) Wariga Concept. The functions of teaching includes (1) Religious Functions, (2) Function of Liberation, (3) Social Functions, and (4) Cultural Functions. Theological Meaning The Day includes (1) God Omnipresent (Wibhu Śakti), (2) God is All-powerfull (Prabhu Śakti), (3) God Omniscient (Jñāna Śakti), and (4) The God is All-creator (Kṛya Śakti).